Body Mass and Body Composition Changes over 7 Years in a Male Professional Rugby Union Team - McHugh, Clíodhna; Hind, Karen; O'Halloran, Aoife; Davey, Daniel; Farrell, Gareth; Wilson, Fiona (International Journal of Sports Medicine, 2021)
The purpose of this study was to investigate longitudinal body mass and body composition changes in one professional rugby union team (n=123), (i) according to position [forwards (n=58) versus backs (n=65)], analysis of players with 6 consecutive seasons of DXA scans (n=21) and, (iii) to examine differences by playing status [academy and international], over 7 years. Players [mean age: 26.8 y, body mass index: 28.9+kg.m2] received DXA scans at fourtime points within each year. A modest (but non-significant) increase in mean total mass (0.8 kg) for professional players was reflected by increased lean mass and reduced body fat mass. At all-time points, forwards had a significantly greater total mass, lean mass and body fat percentage compared to backs (p<0.05). Academy players demonstrated increased total and lean mass and decreased body fat percentage over the first 3 years of senior rugby, although this was not significant. Senior and academy international players had greater lean mass and lower body fat percentage (p<0.05) than non-international counterparts. Despite modest increases in total mass; reflected by increased lean mass and reduced fat mass, no significant changes in body mass or body composition, irrespective of playing position were apparent over 7 years.
Keywords: body composition; dual-energy x-ray absorptiometry; athletes; longitudinal analysis